Sustaining organisational partnerships through authentic connections and engagement : a systemic-governance approach to obesity prevention in a complex health system : a thesis presented in partial fulfilment of the requirements for the degree of Master of Art in Psychology at Massey University, Albany Campus, New Zealand - Nua, Alosina Ellen (Massey University, 2023)
This research explores the ‘systemic-process’ that drew together three organisations trying to sustain an obesity intervention and prevention programme aimed at Māori and Pasifika in a dynamic and complex health system. The purpose was to identify what brought these three organisational partners together, the roles and needs of each of the three partners and how they could work to achieve their collective aims, centred around improving long-term health conditions for Pasifika. This research was part of an evaluation led by my supervisors Professor James Liu and Associate Professor Siautu Alefaio-Tugia. As a Pasifika inside-researcher I have drawn upon Pacific Indigenous Psychology to provide a lens for understanding and contributing new knowledge about what matters most for communities in need. Through talanoa (Pasifika cultural dialogue) with ButtaBean Motivation (BBM), focus group interviews with Total Healthcare (THC) and The Ministry of Health (MoH), and my own cultural-immersion participation, a new governance approach grounded in ‘collective-good’ was uncovered. Key themes that emerged were: shifting in focus towards connections and engagement, applying a perspective in humility and acknowledging what is not working, being open to learning new things and innovative ways of engagement, and resilience-thinking system that is transformative and sustainable based on Pacific-diasporic values and beliefs. Altogether these themes demonstrate the processes that each organisation as a system undertook to collaborate together. Results reveal three key processes that were instrumental in bringing them together: 1) a willingness to collaborate, 2) open to being flexible and adaptive, and 3) a shared goal. Additionally, what has helped them succeed in maintaining the partnership as well as sustaining the weight loss programme ‘From the Couch’ is: fostering good relationships, open communication, good infrastructure, and privileging and supporting Pasifika ways of knowing, doing and being. Through the lens of Pacific-Indigenous psychology this research has found solutions for improving health outcomes for Pasifika in Aotearoa lie within their own people as evidenced through BBM, and through systemic processes as new governance approaches that are based on the ‘collective-good’. Together this provides transformative and sustainable change.
Keywords: 520304 Health psychology